Desarrollo e implementación de una aplicación móvil para la gestión y soporte de las actividades de campo realizadas por el personal operativo de construcciones e instalaciones eléctricas (Coniel Cia. Ltda.) - Loaiza Gonzaga, Andrea Anabell (2015)
In the research work to the Society of buildings and electrical installations Coniel Cia.Ltda City Machala, the need arose to optimize manual processes of daily activities of operational staff, so it was considered to develop the theme thesis entitled "Development and Implementation of a Mobile Application Management and Support Field Activities conducted by the Operational staff Building and Electrical installations (Coniel Cia.Ltda.)", which allowed to solve the absence of a management system operational activities, facilitating the exchange of information leading to efficient processing of data. The project was developed with the methodology of agile software development Mobile D, which ensures an analysis of user requirements and understanding of the business logic for there to focus on system modeling and finally managed the implementation thereof on an Android platform. The application allows portability and versatility when performing tasks such as recording information and photographs of activities carried out by the operating staff (eg changes of meter, new services and change materials), search for customer data, geolocation by friendly, dynamic and easy to understand interfaces, also facilitates the location and transfer between gangs, tracing the route between them, calculating the distance and approximate time, allows the storage of data in each session. For Android Studio development tool for creating applications in an agile and organized jointly with the Java programming language was used; plus the PostgreSQL database manager communicates data to the application using Python web services was used google maps for geolocation crews were also implemented. The tools and programming languages ​​that were used in the development and implementation of the application are free software license, which helped reduce project costs. Therefore, the mobile application developed guarantees agility in the exchange of data in real time, allowing previously entered information is confirmed and validated so that it is a reliable and full active within the company.